Money changes everything how finance made civilization possible - Goetzmann, William N. (Princeton University Press, 2016)
Exploring the critical role of finance over the millennia, and around the world, Goetzmann details how wondrous financial technologies and institutions--money, bonds, banks, corporations, and more--have helped urban centers to expand and cultures to flourish.